Physical activity, depression, anxiety, and stress in adults and elderly in the COVID-19 pandemic in Brazil - Azevedo, Milton José de (2024)
The aim was to verify whether there is a relationship between physical activity habits and the indication of associated risk for depression, anxiety, and stress in adults and the elderly during a period of the COVID-19 pandemic in Brazil. A cross-sectional study, with data collection between October and November 2021, was carried out using an online form, with questions about sociodemographic data, physical activity practice before and during the pandemic, health status, mental health through the Scale of Depression, Anxiety, and Stress (DASS-21), and level of physical activity through the International Physical Activity Questionnaire (IPAQ). Statistical analysis was performed using the chi-square test with a significance level of 5% and multiple correspondence analysis. The were 1044 men and women, aged between 18 and 75, from all over the national territory. Among them, 48.0%, 35.9%, and 61.1% showed an indication of associated risk for depression, anxiety, and stress, respectively. Adult participants 93.4%, female 66.8%, educational level up to undergraduate studies 54.2%, and single 57.5%, as well as those with a low level of physical activity 36.1% and who reported worsening in practice during the pandemic 53.9%, showed a greater risk indication for depression, anxiety and stress (p<0.05). In summary, physically active people who managed to maintain or improve their practice during the pandemic showed a lower indication of associated risk for problems related to mental health. It is important to consider the planning of public policies from the perspective of equity to help people with greater vulnerability in accessing physical activity.